Pengembangan Sistem Informasi Akuntansi Penerimaan Barang Hotel NS Bandung Berbasis Web - Rosalina, Resmi Ranti; Malik, Muhamad Saeful; Abdussalaam, Falaah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The NS hotel application system in the goods receiving department requires extensive time when handling fluctuations in price, quantity, weight, and taxes between incoming goods data and pre-entered purchase orders. Receiving staff must make adjustments in the system through several different screens and menu options, making the process complex and time-consuming. This study aims to simplify the goods receiving system using PHP for programming and MySQL for data storage. This article applies a qualitative research approach through agile development, designed specifically for accounting information systems. The focus is on coordination and communication to ensure the system meets user needs, thereby allowing users more time for clarification, physical control of goods, and streamlining the inflow of goods in daily operations.